Penerapan Model Problem Based Learning dalam Meningkatkan Motivasi dan Prestasi Belajar Ekonomi Peserta Didik Kelas X.2 SMA Negeri 3 Ogan Komering Ulu - Margiyanti (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The low motivation and economic learning achievement of class X.2 students at SMAN 3 Ogan Komering Ulu is caused by teachers not involving students enough in teaching and learning activities. The learning process is dominated by teachers, so students tend to be passive and ultimately result in low student learning outcomes. To overcome this problem, efforts were made to apply a learning model, namely PBL. This research aims to increase the motivation and learning achievement of class This research is classroom action research (PTK) which was carried out in two cycles, with data collection techniques used: written tests, questionnaires, and observation. Data analysis is guided by Descriptive Statistics analysis with percentages. The research results showed that the learning motivation of students in cycle I was 61.69% and cycle II was 72.78%. Meanwhile, students' learning achievement in cycle I obtained an average score of 59.48% and in cycle II an average score of 70.81% was obtained, resulting in an average increase of 11.32%. Based on the research conducted, it can be concluded that the application of the problem-based learning model can increase students' motivation and learning achievement in Economics lessons in class X.2 SMA Negeri 3 Ogan Komering Ulu for the 2022/2023 academic year